Theology in America : Christian thought from the age of the Puritans to the Civil War - Holifield, E. Brooks (New Haven, Yale University Press, 2003)
"The book argues that one important strand of Christian thought was a sustained effort to demonstrate the reasonableness of Christianity while also viewing theology as a "practical" enterprise closely aligned with the aims of religious institutions. The book also describes the emergence of a theology preoccupied with proofs and evidences yet intent on linking theology to the diverse forms of piety in American culture, from revivalist exhortation to high-church ritualism. Holifield locates American theology within the larger European setting, and the clarifies the social location of theology in early America. Finally the author assesses the special importance of Calvinist traditions in the development of American theology and gauges the extent of their influence even on their critics. From Jonathan Edwards to African American theologians, from Anglicans to Transcendentalists, and from New England theology to Presbyterian New School thought, this magisterial book acquaints us with the full chorus of voices that contributed to theological conversation in America's early years."--Jacket.
The New England Calvinists -- Rationalism resisted -- Nature, the supernatural, and virtue -- Jonathan Edwards -- Fragmentation in New England -- The deists -- Evidential Christianity -- Unitarian virtue -- Universal salvation -- Episcopal theology and tradition -- Methodist perfection -- The Baptists and Calvinist diversity -- Restoration -- Roots of black theology -- The immediacy of revelation -- Calvinism revised -- "True Calvinism" defended -- Lutherans : reason, revival, and confession -- Catholics : reason and the Church -- The transcendentalists : intuition -- Horace Bushnell : Christian comprehensiveness -- The Mercersburg theology : communal reason -- Orestes Brownson and Isaac Hecker : transcendental Catholicism -- The dilemma of slavery.
Includes bibliographical references (pages 513-595) and index.
Keywords: Theology, Doctrinal -- United States -- History